2015
DOI: 10.1016/j.crhy.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Spin fluctuations in iron pnictides and chalcogenides: From antiferromagnetism to superconductivity

Abstract: The present article reviews recent experimental investigations of spin dynamics in iron-based superconductors and their parent compounds by means of inelastic neutron scattering. It mainly focuses on the most contemporary developments in this field, pertaining to the observations of magnetic resonant modes in new superconductors, spin anisotropy of low-energy magnetic fluctuations that has now been observed in a wide range of chemical compositions and doping levels, as well as their momentum-space anisotropy i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 405 publications
(583 reference statements)
3
101
0
1
Order By: Relevance
“…such as neutron scattering [10][11][12][13][14] and / or X-Ray Scattering [15,16]. Neutron scattering experiments confirmed the presence of sizable magnetic moments in Fe pnictides (on the order of ≈ 1 µ B ) [2,3,10] with few exceptions, such as NaFeAs that shows lower ordered magnetic moment [2,3].…”
mentioning
confidence: 73%
“…such as neutron scattering [10][11][12][13][14] and / or X-Ray Scattering [15,16]. Neutron scattering experiments confirmed the presence of sizable magnetic moments in Fe pnictides (on the order of ≈ 1 µ B ) [2,3,10] with few exceptions, such as NaFeAs that shows lower ordered magnetic moment [2,3].…”
mentioning
confidence: 73%
“…Since magnetism may be responsible for many of the anomalous transport properties and origin of high-T c superconductivity in these materials 6 , previous efforts focused on understanding the evolution of magnetism as superconductivity is induced by electron or hole-doping to their AF parent compounds 3,[7][8][9] . In the case of copper oxides, spin excitations in hole-doped superconductors are marked by an hourglass-like dispersion 3 and a neutron spin resonance coupled with superconductivity 2 .…”
Section: (A)]mentioning
confidence: 99%
“…4,5 is their close proximity to a static antiferomagnetic (AF) ordered parent compound [6][7][8][9] . Since magnetism may be responsible for many of the anomalous transport properties and origin of high-T c superconductivity in these materials 6 , previous efforts focused on understanding the evolution of magnetism as superconductivity is induced by electron or hole-doping to their AF parent compounds 3,[7][8][9] .…”
Section: (A)]mentioning
confidence: 99%
“…The observation of neutron spin resonance within a broad range of materials, in particular high-T c cuprates [1], iron pnictides [2,3], and heavy-fermion superconductors [4][5][6], is recognized as an indicator of unconventional superconductivity. It was shown that sign-changing gap symmetry can lead to the existence of resonance behavior [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%